Usefulness and Limitations of Animal Models of Venous Thrombosis - Levi, Marcel; Dörffler-Melly, Janine; Johnson, Gerhard J.; Drouet, Ludovic; Badimon, Lina (Thrombosis and Haemostasis, 2001)
To study the pathogenesis of in vivo thrombus formation and to evaluate novel preventive or therapeutic strategies, animal models of venous thrombosis have been in use for more than 50 years. In the past decades numerous animal models of venous thrombosis have been developed and have been applied for a variety of objectives and mostly without certain predictive value for the relevance to human venous thrombosis. The Subcommittee on Animal, Cellular, and Molecular Models of Thrombosis and Haemostasis of the Scientific and Standardization Committee of the International Society on Thrombosis and Haemostasis decided to systematically review the various animal models of venous thrombosis and to analyze the contribution of these models to the study of the pathogenesis and treatment of venous thrombosis. This manuscript summarizes the results of this analysis and it draws some conclusions on the appropriate use of animal models for venous thrombosis.